Using Pazia Angklung application in understanding song scores - Maulana, A C; Julia, J (Journal of physics. Conference series, 2019)
Playing a music score, students have difficulty reading scales and understanding the score of a song. These difficulties must be overcome with the Pazia Angklung application. This research aims to improve students' understanding in music notation. The study was conducted by following the procedure as follows: (1) searching and downloading application related to musical instruments to play song scores; (2) learns the application to understand the scale; (3) play music scores using the application; and (4) evaluating. The study was conducted in fourth-grade elementary students with an age range of 9-11 years. Total subjects were 26 students. The results showed that learning the parts in the song by using the Pazia Angklung application, can improve the effectiveness of learning. It can be concluded, that the skills of the students in the song section are increasing well, so are some aspects of the attitude.